1999
DOI: 10.1111/j.1151-2916.1999.tb02042.x
|View full text |Cite
|
Sign up to set email alerts
|

Sintering of Lanthanum Zirconate

Abstract: Lanthanum zirconate (La 2 Zr 2 O 7 ) was prepared by coprecipitating lanthanum nitrate and zirconyl oxychloride at pH 10, followed by ethanol washing. The initial high surface area of ∼304 m 2 ؒg −1 decreased very rapidly with increased sintering temperature and decreased to an immeasurably small value after heating at 1200°C for 15 h. The major parameters studied were phase evolution, crystallite size, porosity, surface area reduction, and shrinkage during sintering. Three temperature regions were identified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
21
0
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 20 publications
6
21
0
1
Order By: Relevance
“…For samples A0-A4, four Raman bands at 299, 395, 490 and 515 cm −1 are visible. These Raman bands are the characteristics of LZ-type structure, which is consistent with the previous results [18]. One Raman band at 375 cm −1 is also detected in A1-A4, which is the characteristics of LaYO 3 according to the Raman spectrum of pure LaYO 3 .…”
Section: Characterization Of La 2 O 3 -Zro 2 -Y 2 O 3 Bulk Ceramicssupporting
confidence: 89%
“…For samples A0-A4, four Raman bands at 299, 395, 490 and 515 cm −1 are visible. These Raman bands are the characteristics of LZ-type structure, which is consistent with the previous results [18]. One Raman band at 375 cm −1 is also detected in A1-A4, which is the characteristics of LaYO 3 according to the Raman spectrum of pure LaYO 3 .…”
Section: Characterization Of La 2 O 3 -Zro 2 -Y 2 O 3 Bulk Ceramicssupporting
confidence: 89%
“…For the three specimens, four Raman bands at 299, 395, 490 and 515 cm −1 are visible. These Raman bands are the characteristics of LZ-type structure, which is consistent with the previous results [19]. One Raman band at 375 cm −1 is also detected in three specimens, which is the characteristics of LaYO 3 according to the Raman spectrum of pure LaYO 3 .…”
Section: Phase Structure Of the Coatingsupporting
confidence: 89%
“…The use of sintered glass for the matrix has the important advantage of allowing relatively low processing temperatures (< 700 C), much lower than the sintering temperature required for densification of pyrochlore crystalline ceramics, which is about 1200 C. [32,33] The processing temperature for a glass powder based approach will also be lower than the temperatures required for crystallization of host phases in conventional glass-ceramics, which are usually well above 1000 C. [2,17] Moreover densification by sintering and hotpressing has the additional advantage of avoiding devitrification and phase separation problems occurring in glass melting processes. [2,3] In a previous study, [30] we demonstrated the fabrication of La 2 Zr 2 O 7 pyrochlore-glass composites by powder technology and sintering.…”
mentioning
confidence: 99%